Spring-Assisted Cranial Expansion for Multisuture Craniosynostosis: First Case Report from the Indian Subcontinent - Gujjalanavar, Rajendra S.; Doddamani, Rajalaxmi; Deraje, Vybhav; Gopal, Swaroop (Indian Journal of Plastic Surgery, 2023)
We present a first use case report from the Indian subcontinent of a 5-month-old child with multisuture craniosynostosis with raised intracranial pressure managed by spring-assisted cranial expansion followed by traditional fronto-orbital advancement and cranial vault remodeling. We emphasize the advantages of spring-assisted cranial expansion in extremely young infants with raised intracranial pressure over posterior vault distraction osteogenesis and open posterior vault remodeling.
Keywords: spring-assisted cranial expansion; posterior vault expansion; multisuture craniosynostosis